The Interplay of International Students’ Acculturative Stress, Social Support, and Acculturation Modes - Sullivan, Christopher; Kashubeck-West, Susan (Journal of International Students, 2015)
This study examined the relationship between acculturation modes (assimilation, integration, separation and marginalization), social support, and acculturative stress in undergraduate and graduate international students (N=104) at a medium-sized public university in the Midwestern United States. The study found that international students with broad-based social support and an Integration approach to acculturation experienced lower levels of acculturative stress. Implications for more effective counseling with international students are addressed.